The Effect Of Organizational Activity On Timely Graduation Of Medical Students In The Academic Stage Of 2020 - A. Muh. Naufal Abiyyu; Sri Wahyuni Gayatri B; Windy Nurul Aisyah; Shulhana Mochtar; Marlyanti Nurrahmah (Sean Institute, 2025)
This study aims to analyze the effect of organizational activity on the timely graduation of medical students of the 2020 academic phase at the Muslim University of Indonesia. Medical students must balance academic, organizational, and social life commitments that can affect academic performance and the duration of study. In addition to organizational activity, other factors such as time management, parental support, learning motivation, and academic load also play a role in determining the length of study. This study used an analytical observational method with a cross-sectional design . The sample consisted of 100 students selected using a purposive sampling method. Data were collected through questionnaires and analyzed using the chi-square test with a significance level of 0.05. The results showed that 89% of students were active in organizations and 65% graduated on time. However, no significant relationship was found between organizational activity and timely graduation with a p value = 0.441 (more than 0.05). This finding suggests that other factors, especially time management and learning motivation, may have a greater influence on students' academic success. Further research is recommended to explore additional variables and expand the number of samples to obtain more comprehensive results.